Multiple challenges in the development of commercial crops using CRISPR technology - Ayub, Nicolás Daniel (2023)
The CRISPR/Cas system is a highly efficient and versatile tool for editing plant genomes, with the potential to accelerate breeding programs and improve the sustainability of food production. Nevertheless, technical limitations delay the rapid spread of the CRISPR/Cas system benefits in agriculture. The natural features of plant species, including reproductive behavior, ploidy levels, genetic diversity, and generation times, can significantly impact the introgression of edited traits into elite germplasms. The production and selection of edited events require the same level of effort as those of their transgenic equivalents. Additionally, edited alleles tend to be recessive or not fully dominant, which differs from dominant transgenic events. To accelerate the introgression of edited events into conventional and transgenic varieties, we suggest utilizing edits on single-copy genes that induce dominant mutations. In the absence of new, simple traits that provide exceptional economic benefits for large companies, like herbicide tolerance in transgenic crops, we propose the emergence of particular public grants for edited variety productions, especially when the introgression shows a high level of technical feasibility. In the context of climate change, these public actions must be taken quickly to alleviate significant reductions in crop production.